Formy obecności filmu w literaturze fikcjonalnej = Forms of film`s presence in literary fiction - Jazownik, Maria; Jazownik, Leszek (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
In the discussions of the relationships between film and literature, the influence of the latter on the former is usually accented. The opposite dependences are rarely addressed as they, seemingly, appear to be incidental and of lesser importance. Nonetheless, they create a wide spectrum of diverse phenomena which, however, has not been satisfactorily researched yet. For this reason, in the paper an attempt has been made to register and typologize various forms of intertextual film "presences" in fiction.
Keywords: film vs. literature; film issues in literature; intertextuality; film; literatura a film; problematyka filmowa w literaturze; intertekstualność